Outcomes in patients who underwent a concomitant tricuspid valve procedure during left ventricular assist device implantation. Issue 12 (15th November 2019) - Critsinelis, Andre; Kurihara, Chitaru; Kawabori, Masashi; Sugiura, Tadahisa; Loor, Gabriel; Frazier, O. H.; Morgan, Jeffrey
Abstract: Background: Study findings have been inconsistent regarding whether a concomitant tricuspid valve replacement or repair performed concurrently with continuous‐flow left ventricular assist device (CF‐LVAD) implantation has additive clinical benefit in patients with severe tricuspid valve regurgitation (TR). Aim of Study: To determine the effect of performing a concomitant tricuspid valve procedure (TVP) at the time of CF‐LVAD implantation on patient outcomes. Methods: We retrospectively reviewed our single‐institution experience in 526 patients who underwent primary implantation of a CF‐LVAD between November 2003 and March 2016. We identified 59 (11.2%) patients who had severe TR at the time of implantation and analyzed the effect of performing a concomitant TVP at the time of CF‐LVAD implantation on the rate of survival, incidence of postoperative right heart failure (RHF), recurrence of TR, and incidence of 30‐day readmission. Results: We did not observe a significant difference in the overall survival rate ( P  = .51), incidence of postoperative RHF ( P  = .26), or recurrence of TR ( P  = .73) between patients with severe TR who underwent a TVP and those who did not at the time of CF‐LVAD implantation. However, the incidence of 30‐day readmission was significantly lower in patients who underwent a TVP than in those who did not ( P  = .002). Conclusions: Performing a concomitant TVP at the time of CF‐LVAD implantation did not improve patient outcomes but reduced the incidence of 30‐day readmission.